Stimulation and Isolation of Paraphysoderma sedebokerense (Blastocladiomycota) Propagules and Their Infection Capacity Toward Their Host Under Different Physiological and Environmental Conditions - Asatryan, Armine; Boussiba, Sammy; Zarka, Aliza (Frontiers in Cellular and Infection Microbiology, 2019)
Paraphysoderma sedebokerense (P. sedebokerense) (Blastocladiomycota) is a facultative pathogenic chytrid that causes irreversible damage to some green microalgae. Specific attacks leading to culture collapse under different conditions have only been described in the lucrative microalga Haematococcus pluvialis (H. pluvialis), while generating biomass for ketocarotenoid astaxanthin production, both indoors and outdoors. In order to manage the infection, parasite propagules (zoospores/amoeboid swarmers), the initiators of the disease, must be studied. Until now, no report on isolated P. sedebokerense propagules has been published. Here, we report on a reproducible method for the stimulation of P. sedebokerense propagule release and their isolation from fungal cultures in synthetic media and infected H. pluvialis cultures, and we further studied their development under different conditions. The isolated propagules featured different spore morphotypes, with coatless spherical spores and amoeboid swarmers being the most dominant in the first pulse of propagule release in both cultures. Inoculating the pure propagules with the host, in both the presence and absence of nitrogen, resulted in epidemic development in both green and red cells; however, in red cells, the epidemic developed more quickly in the presence of nitrogen. Biologically non-active autoclaved host cells were used to distinguish the initial stages of recognition from more progressive stages of the epidemics; on these cells, propagules encysted but did not develop further. These results prove the existence of heat-stable recognition sites on the host and an obligatory signal transduction from the host to support fungal cyst development. The propagule isolation method described herein is a breakthrough that will enable researchers to study the influence of different substances on the propagules, specifically as the initiators of the infection, and thus assist in the management of chytrid diseases. Moreover, it will be useful in studying host-parasite recognition and, therefore, will increase our understanding of the multiple chytrid infections found in nature.